Psychometric Properties of the Existence Subscale of the Purpose in Life Questionnaire for Chinese Adolescents in Hong Kong - Ben M. F. Law (The Scientific World Journal)
The current study aims to test the psychometric properties of the Existence Subscale of the Purpose in Life Questionnaire (EPIL) for early adolescence. The Purpose in Life Questionnaire (PIL), originally created by Craumbaugh and Maholick, is a 20-item scale measuring different dimensions of life purposes. The current study selected seven items representative of the existence dimension to form another scale, the EPIL. The analysis was based on 2842 early adolescents, ranging from 11 to 14 years old. Principal axis factoring found one factor, with 60% variance being explained. Cronbach’s alpha for the EPIL was 0.89, which was high. The factor structure was stable across genders. Criterion-related validity was determined when the scale was used to differentiate volunteers and nonvolunteers. Construct validity was found when the scale was associated with life satisfaction. The results give support to the fact that the EPIL could be used alone to measure the psychological well-being of early adolescents and the appropriateness of the EPIL in adolescent research.